MiraBR – A System for Patent Analysis - Nolasco, Diogo; Oliveira, Jonice (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Innovation is essential for economic and technological development, with patents serving as a key metric to monitor and stimulate this innovation. However, patent information is often fragmented and distributed across isolated systems, hindering strategic and global analyses. Problem: The lack of integration between patent databases limits the ability to conduct comparative and evolutionary analyses, thereby restricting efforts to identify trends, prospect opportunities, and monitor international competitiveness. Solution: The MiraBR system was developed as an open-source web application that collects, integrates, and analyzes patent data from multiple national and international sources. Using a web crawler, data is extracted from databases such as INPI, Derwent, and Espacenet, processed, and integrated into a centralized database. The system supports multi-language search queries and enables analyses based on classifications, countries, inventors, and patent holders. It also provides intuitive visualizations that facilitate strategic and comparative analysis. IS Theory: This work is conceived under the Socio-technical theory, as the system integrates human and technical elements. Method: The research involved a proof of concept to validate the system’s core functionalities and a quasi-experiment to assess its usability and effectiveness in real-world scenarios. The quasi-experiment included specialists from the intellectual property field, who evaluated the system’s performance and relevance through practical application and structured questionnaires. The analysis approach was descriptive, aiming to present the system’s capabilities and its alignment with user needs, with a focus on quantitative metrics (e.g., precision and recall) and qualitative feedback (e.g., usability assessments). This mixed-method approach ensured a comprehensive evaluation of the system, addressing both technical performance and user satisfaction. Results: The system was evaluated by INPI experts and received high approval for its ease of use, rich visualizations, and quality of the analyses. Precision and recall metrics indicated satisfactory performance in information retrieval. Contributions: MiraBR contributes to innovation management by enabling integrated strategic analyses of patents, enhancing technological support for science and innovation in Brazil. It also paves the way for future research in data mining and visualization applied to the domain.